Literature Circles Strategy as a Support for EFL Students’ Reading Comprehension Skills and Motivation - Jawad, Zainab (Al-Adab Journal, 2024)
The current study aims to explore the impact of using literature circles strategy on supporting EFL college students ‘reading comprehension skills and motivation towards reading. Literature circles strategy is an activity in which the students meet to discuss and react to a text, book or short story which they are reading together. This research is an experimental one in which thirty college students in the experimental group were taught the short story (The Dolle’s House) by using the literature circles strategy, whereas the other thirty students in the control group were taught the same short story by using the conventional method. To achieve the aims of this study, an observation checklist of reading comprehension skills and a questionnaire of motivation toward reading have been administered by the researcher to get the necessary data. The findings reveal that the experimental group’s students performed better than the control group’s students with significant differences favoring the experimental group that was exposed to literature circles strategy. Pedagogical implications for EFL college teachers are presented to enhance and improve their students’ language learning by incorporating the literature circles strategy in EFL classrooms especially in teaching short stories and novels to support students ‘reading comprehension skills and motivation toward reading.